KARAKTERISASI PADUAN AlMgSi UNTUK KELONGSONG BAHAN BAKAR U3Si2/Al DENSITAS URANIUM 5,2 gU/cm3 - Ginting, Aslina Br.; Supardjo; Yanlinastuti, Yanlinastuti; Anggraini, Dian; Boybul, Boybul (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
Increase in uranium density from 2.96 gU/cm3 to 5.2 gU/cm3 of U3Si2/Al fuel requires a compatible cladding. High density fuel possesses high hardness value, and the use of AlMg2 as cladding material may cause dog bone during rolling process. In addition to dog bone phenomena, swelling can also occur during the use of nuclear fuel in the reactor due to rising in fission products and burn up. For this reason, substitution of cladding material should be determined to suit the high density U3Si2/Al fuel. This research deals with the characterization of AlMgSi as a candidate for AlMg2 substitution. The characterization includes thermal analysis with DTA (Differential Thermal Analysis) dan DSC (Differential Scanning Calorimetry), hardness test with macrohardness tester, microstructure examination with SEM (Scanning Electron Microscope), and corrosion analysis by heating at 150 °C for 77 hours in an autoclave. Analysis results show that both AlMgSi and AlMg2 share stable heat compatibility with U3Si2/Al up to 650 °C. AlMgSi cladding has a hardness value of 115 HVN, higher than that of AlMg2, which is 70.1 HVN. Microstructure examination shows that AlMgSi has better morphology of interface bonding than AlMg2. Corrosion rate analysis also indicates that AlMgSi has lower corrosion rate. The results of thermal, hardness, microstructure and corrosion characterization reveal that the U3Si2/Al fuel of 5.2 gU/cm3 suits better with AlMgSi than AlMg2.